THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN THE DEVELOPMENT OF THE SCIENCE OF PEDAGOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the role of modern pedagogical technologies in the development of pedagogy. It is also based on the need to conduct training on the basis of pedagogical technology, to use modern technical tools, computers, multimedia complexes with video-computers in the course of the lesson. The concept of pedagogical technology is also reflected in scientific articles, periodicals, conference topics and reports, and scientific works of scientists dealing with this subject are also covered. In addition, conclusions and suggestions on increasing the role of modern pedagogical technologies in the development of the science of pedagogy have been developed.